Avaliação morfológica e das dimensões anatômicas do canal nasopalatino. Análise por tomografia computadorizada cone beam (TCCB). - Mendes, Flavia Maria Ferreira (2021)
The nasopalatine canal (NPC) is an important structure located in the premaxilla connecting the oral with the nasal cavity in the anterior region, containing the nasopalatine nerve and the descending branch of the nasopalatine artery. The evaluation of the CNP is especially important for the planning and execution of surgical procedures performed in the maxilla as apicectomy of central incisors, cyst lesion enucleation, surgically assisted maxillary expansion, etc. The objective of this work was to evaluate the morphology and dimensions of the nasopalatine canal, as well as its correlation with age and gender through cone-beam computed tomography (CBCT) images. Eighty-six CBCT scans of patients aged between 18 and 82 years were evaluated by a unique calibrated evaluator. NPC was morphologically classified into single, parallel and Y-Shape. The following anatomical measurements were taken: #1 NPC diameter at the level of the nasal cavity; #2 NPC diameter at the level of the oral cavity; #3 length of NPC; #4 distance between the buccal wall of the NPC and the buccal bone plate (oral level); # 5 distance between the buccal wall of the NPC and the buccal bone plate (nasal level); #6 distance between the bone crest and the opening of the incisive foramen. #7 distance between the buccal wall of the NPC and the root of the maxillary central incisors. It was observed that the single channel was present in 65.51% of patients. Morphometric analysis showed that the diameter of the NPC at the oral level (#2) was 3.83 mm for men and 3.45 mm for women (p=0.0034). The length of the NPC (#3) was 12.96 and 10.57 mm between males and females, respectively (p<0.001). Measure #6 had a higher value for men (8.20mm) than for women (6.80mm) (p<0.001). Weak positive correlation was found between anatomical measurements and age. It was concluded that the single NPC is the most prevalent, and that the anatomical dimensions are related to gender, so that men have higher measurements comparing to women.